On two initial boundary value problems for the generalized KdV equation - Faminskii, A.V. (Нелинейные граничные задачи, 2004)
Results on nonlocal well-posedness are established for initial boundary value problems for the generalized KdV equation in a bounded rectangle and a half-strip under natural assumptions on initial and boundary data. The considerable part of the study is devoted to special solutions of the linearized KdV equation of the "boundary potential" type.